ASUHAN KEPERAWATAN POLA NAPAS TIDAK EFEKTIF PADA An. C DENGAN ASMA BRONKIAL DI RUANG PARIKESIT RST WIJAYAKUSUMA PURWOKERTO - Endah Wulan Ramadhani,; Ikit Netra Wirakhmi,; Atun Raudotul Ma’rifah, (JURNAL PENGABDIAN MANDIRI, 2022)
Asthma is a disease that occurs due to the narrowing of the airways due to inflammation. This disease usually presents with symptoms such as wheezing, shortness of breath, chest tightness, and variable cough and variable airflow limitation. Efforts made in children with asthma to control the recurrence of asthma are to keep children away from agents that can make asthma relapse such as dust, animal dander, weather changes. This study uses a qualitative descriptive method in the form of a case study, the case study in this study examines how to reduce shortness of breath in asthmatics, starting from setting the Fowler's position or semi-Fowler's position, teaching effective coughing techniques and collaboration with pharmacology. The results of the study indicate that the problem occurs in the client can be resolved in 3 days which is characterized by decreased shortness of breath, decreased use of accessory muscles, decreased expiratory phase lengthening, and normal breathing frequency, after the action for 3 days the problem of ineffective breathing patterns has been resolved.